Barriers to intra-familial prevention of type 2 diabetes: A qualitative study on horizons of significance and social imaginaries. (June 2020) - Grabowski, Dan; Andersen, Tue Helms
Objectives: In families living with type 2 diabetes, relatives have a significantly heightened risk of developing the disease. In many families, both the person with type 2 diabetes and his/her relatives lack detailed knowledge about this risk. One obstacle to constructive intra-familial prevention and risk reduction is the lack of perceived familial disease relevance. The objective of the present study is to explore barriers to prevention in families with at least one adult with type 2 diabetes. Methods: Data were gathered during eight problem assessment and ideation workshops with families. The data were analyzed using radical hermeneutics and interpreted using Taylor's concepts of social imaginaries and horizons of significance. Results: The analysis revealed three main barriers: (1) Sole responsibilities and the absence of collective practices, (2) intra-familial differences in perceptions of risks and future health, and (3) lack of perceived disease significance and the ensuing lack of mutual care. The participating families all experienced one or more of the three identified primary barriers. Discussion: The study has produced important knowledge about barriers to familial prevention of type 2 diabetes. The findings confirm that familial prevention is indeed a complex matter that calls for the use of complexity-oriented approaches in health care practice.